The effect of exercise interventions on resting metabolic rate: A systematic review and meta-analysis. Issue 14 (17th July 2020) - MacKenzie-Shalders, Kristen; Kelly, Jaimon T.; So, Daniel; Coffey, Vernon G.; Byrne, Nuala M.
ABSTRACT: The systematic review and meta-analysis evaluated the effect of aerobic, resistance and combined exercise on RMR (kCal·day -1 ) and performed a methodological assessment of indirect calorimetry protocols within the included studies. Subgroup analyses included energy/diet restriction and body composition changes. Randomized control trials (RCTs), quasi – RCTs and cohort trials featuring a physical activity intervention of any form and duration excluding single exercise bouts were included. Participant exclusions included medical conditions impacting upon RMR, the elderly (≥65 years of age) or pregnant, lactating or post-menopausal women. The review was registered in the International Prospective Register of Systematic Reviews (CRD 42, 017, 058, 503). 1669 articles were identified; 22 were included in the qualitative analysis and 18 were meta-analysed. Exercise interventions (aerobic and resistance exercise combined) did not increase resting metabolic rate (mean difference (MD): 74.6 kCal·day -1 [95% CI: −13.01, 161.33], P = 0.10). While there was no effect of aerobic exercise on RMR (MD: 81.65 kCal·day -1 [95% CI: −57.81, 221.10], P = 0.25), resistance exercise increased RMR compared to controls (MD: 96.17 kCal·day -1 [95% CI: 45.17, 147.16], P = 0.0002). This systematic review effectively synthesises the effect of exercise interventions on RMR in comparison to controls; despite heterogenous methodologies and high risk of bias within included studies.